Силур Подолии: путеводитель экскурсии - Цегельнюк П. Д.; Гриценко В. П.; Константиненко Л. И.; Ищенко А. А.; Айзенверг Д. Е. Давид Ефремович (Киев, Наукова думка, 1983)
Сост. указаны на обороте тит. л.